Organizations and the media : - Pallas, Josef; Strannegard, Lars; Jonsson, Stefan, 1961- (Routledge studies in management, organizations and society, 2014)
"The relationship between media and the organizations they cover has changed dramatically in the last few decades, which have witnessed a huge expansion of news coverage focusing on different types of organizations and their activities. In parallel, organizations have dramatically increased their investment in Public Relations and other media-oriented forms of communication. Like other societal developments--globalization, marketization, individualization, scientification--mediatization has become an institutional force.This book analyses the mediatization of contemporary organizations and how individual organizations, industry or markets are scrutinised. It examines its key influence on the actions of organizations, thereby shaping the entire landscape in which the organizations operate. What such a perspective provides is the accentuation of the interplay between organizations and different parts of the society as embedded in the media and its logic. This will be essential reading for professionals, academics and advanced students in Organizational Studies, Public Relations and Media Studies" -- Από τον εκδότη.